THE ROLE OF MULTICULTURAL EDUCATION IN THE ERA OF GLOBALISATION: BUILDING TOLERANCE, REDUCING DISCRIMINATION, AND STRENGTHENING CHARACTER AND NATIONAL IDENTITY THROUGH A LITERATURE REVIEW - Rizki Fauzi; Suhari Suhari (Adisam Publisher, 2025)
This study aims to analyse the role of multicultural education in building tolerance, reducing discrimination, and strengthening national character and identity in the era of globalisation. The research approach used is qualitative with a literature review method, which examines various scientific sources on the theory, practice, and policy of multicultural education. The results of the study show that multicultural education plays an important role as a means of forming mutual respect between individuals and groups with different social, cultural, and religious backgrounds. Through the implementation of an inclusive curriculum and a learning environment that respects diversity, multicultural education has proven to be effective in fostering values of tolerance and equality, as well as preventing discriminatory attitudes in society. In addition, multicultural values integrated with the principles of Pancasila and national culture contribute to strengthening character, morality, and a sense of nationality among students. Therefore, multicultural education needs to be positioned as a key strategy in shaping a generation with superior personalities, a nationalistic spirit, and the ability to adapt constructively in the midst of globalisation.